Low Energy Properties of Baryons In Phenomenological Models - Gilhotra, Vani (My University, 2012)
Low energy properties of Baryon octet are analyzed here by using various approaches. We take nucleons in addition to other baryon octets for determining fundamental properties. Here the baryon is considered to be made up of the sea and valence part where sea is assumed to have various fock states in addition to the three valence quarks. Here the sea comes with the different contents contributing to the spin 0,1,2 depending whether scalar, vector and tensor sea. Here we have a statistical approach to study the behavior of nucleons in contributing to these properties and hence the different approaches where the similar framework has been used is studied for the respective properties. We have used a statistical model in which a nucleon is taken as an ensemble of quark-gluon Fock states and where a probability to find a Fock state is decided by the principle of balance or principle of detailed balance. Within this framework, various models have been discussed for these properties and their domain of validity is check for calculating these parameter to find the effects of the sea for them. Our aim in the thesis is to find out various approaches to calculate these fundamental properties of the baryon octets and to analyze the difference in various approached based on the dynamics of the sea contributions. We calculate the coefficient coming from this sea in terms of α & β. We see the effect of sea contribution on different models just by considering the sea or by suppressing it. Hence we get the different values of α & β for both the approaches which show the importance of these contributions coming from various fock states and hence put a contain on the values of alpha and beta. The results for these properties baryon showing the different values in different models. For betterment for our analysis we have also taken few other theoretical models and properties calculated in them and then we have shown a comparison between these models. Some shows higher relevancy to the experimental values while some shows less. Thus we tabulate the different results validating these models.
M.Sc. (Physics)
Keywords: Phenomenological Models